2008
DOI: 10.1055/s-0028-1083159
|View full text |Cite
|
Sign up to set email alerts
|

Facile and Highly Regiospecific Synthesis of 2-Aryl-Substituted Pyrazolidin-3-ones from α,β-Unsaturated N-Acylbenzotriazoles and Arylhydrazines

Abstract: The bis-addition of arylhydrazines to a,b-unsaturated Nacylbenzotriazoles to form heterocyclic compounds was achieved in refluxing THF by using triethylamine as promoter. The reaction was highly regioselective and various 2-aryl-substituted pyrazolidin-3-ones were obtained in moderate to good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9] N-acylbenzotriazoles are one of the most useful benzotriazolederivatives which have been successfully utilized to prepare numerous biologically relevant compounds under neutral and mild conditions by N-, C-, S-, and O-acylations. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] In recent years our group has been involved in exploration of the synthetic utility of N-acylbenzotriazoles to make sugar amides by N-acylation, 25 benzoxazoles and N-phenylamides by benzotriazole ring cleavage 26,27 and ureas, carbamates and thiocarbamates by the Curtius rearrangement. 28 The earlier synthetic methods for conversion of carboxylic acids to N-acyl benzotriazole i.e.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] N-acylbenzotriazoles are one of the most useful benzotriazolederivatives which have been successfully utilized to prepare numerous biologically relevant compounds under neutral and mild conditions by N-, C-, S-, and O-acylations. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] In recent years our group has been involved in exploration of the synthetic utility of N-acylbenzotriazoles to make sugar amides by N-acylation, 25 benzoxazoles and N-phenylamides by benzotriazole ring cleavage 26,27 and ureas, carbamates and thiocarbamates by the Curtius rearrangement. 28 The earlier synthetic methods for conversion of carboxylic acids to N-acyl benzotriazole i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Low boiling point of dichloromethane and high solubility of large variety of carboxylic acid in it made dichloromethane as first preference for our reaction. Lastly, through temperature optimization we tried to find out the variation in yields by varying temperature of reaction from 0-35 °C and observed no change at all in yields (entries [13][14][15]. This reaction was also tried with two different disulfides, i.e.…”
Section: Scheme 3 Prototype Reaction For the Synthesis Of N-acylbenzomentioning
confidence: 99%
“…Now a day's chemist focused on development of new antimicrobial agents which will resolve the resistant issue to produce good anti-infective agents [2][3][4][5] . Azole fused with benzene ring, such as benzimidazoles and benzoxazole containing 2 or 3 hetero atoms possess various medicinal properties [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] . It is reported that benzimidazole is an important class of heterocyclic compound which are associated with various pharmacological activities e.g: antioxidant 21 , anticancer 22 , anthelmintic 23 , antihypertensive 24 , antiviral 25 , antiinflammatory 26 , antihistaminic 27 , analgesic 28 , antiprotozoal 29 , antiulcer 30 , anticoagulant 31 , anticonvulsant 32 , antifungal 33 , antihepatitis B Virus 34 , and antibacterial activity 35 .…”
Section: Introductionmentioning
confidence: 99%